REVISITING RECRUITMENT FOR SUSTAINABLE DEVELOPMENT: A STUDY OF JOB PREFERENCES OF WOMEN INITIAL JOB SEEKERS IN MALAYSIAN ISLAMIC FINANCE INDUSTRY (International Journal of Psychosocial Rehabilitation, 2020)
Albeit, women talented undergraduate initial job seekers dominate the contemporary scarce labour market, they are under engaged and underrepresented in the corporate recruitment pipeline. Hence, the need to revisit the talent pipeline for competitiveness and success in ongoing talent war especially, in ensuring sustainable development at least within the Islamic finance industry. This study calibrates the factors (job attributes) that determine job preference of women initial job seekers, trends in trade-offs by calculating willingness to pay (WTP) and the uptake rates. Taking cognisance of limitations of isolation methods used in past research, this study employed DCE, a unique methodology that provides significance, relative importance and the cost-effectiveness of human resource interventions in multiple-criteria choice situations. Based on signalling theory, social identity and gender role socialisation theories seven identified job attributes (CSR and traditional job attributes) were used in a questionnaire-based census survey to determine the selected population’s job preference. Findings from conditional logit model revealed a positive significance and relative importance of all attributes, with CSR attributes (job security, training and development, and work life balance) found to be more significant, relatively important and cost- effective than traditional job attributes (salary, career advancement and location of employers) though, donation is the least preferred. Also, the moderating effect of academic performance on preference revealed a marginal difference among cohorts. This study combines traditional job attributes with CSR a rarely used approach in job preference literature. This study also provides cost implications of provision of attributes and the need for managers to design jobs that attract different groups of women in the Islamic finance labour market.